Exploring Dynamic Brand Experience through Co-Creation and E-WOM: Implications for Consumer Equity in Social Media Marketing - Moazzam Hussain Qadri; Sohail Khan; Narmeen Tariq; Umer Shahid (Indus Journal of Social Sciences, 2025)
Within the framework of social networks, this research investigates the function that dynamic brand experience may play as a marketing tool for companies. We want to know how co-creating value impacts the dynamic brand experience, based on the source and motive. The study also examines the link between dynamic brand experience and consumer equity, as well as the moderating impact of electronic word-of-mouth (E-WOM). A dynamic brand experience may be positively impacted by the source and motive of value co-creation. Customers’ brand equity and dynamic brand experience are also positively correlated. As for the link between a dynamic brand experience and consumer equity, E-WOM serves as a moderator.